Synthesis and characterization of fullerene doped polyaniline/titanium dioxide nanocomposites for electromagnetic interference shielding / Nurrafiqah Mokhtar - Nurrafiqah , Mokhtar (2018)
Fullerene doped Polyaniline (PAni) nanocomposites were synthesized through template-free method at 0°C by using aniline (Ani) as monomer, fullerene and titanium dioxide (TiO2) as fillers. Fullerene doped PAni nanocomposites with chemical treatment by sulfonic groups such as dioctyl sodium sulfosuccinate (AOT), sodium dodecylbenzene sulfonicate (DBSA) and camphorsulfonic acid (CSA) were prepared to improve the dispersion of C60 during polymerization. Besides, PAni nanocomposites with different types of fullerene (C60 and small gap fullerene (S.G.F)) and PAni nanocomposites with different contents of C60: (5 %, 10 %, 15 %, 20 % and 40 %) were synthesized. Fourier Transform Infrared (FTIR) and Ultraviolet-visible (UV-vis) spectra validated the functional groups and conducting behavior of fullerene doped PAni nanocomposites, respectively. The existence of fillers in PAni nanocomposites were confirmed by the characteristic peaks of TiO2 and fullerene (C60 and S.G.F) in X-ray diffraction (XRD) pattern. The morphology behaviors and electrical conductivity of fullerene doped PAni nanocomposites were investigated by Field Emission Scanning Electron Microscope (FESEM) and resistivity meter, respectively. Fullerene doped PAni nanocomposites with chemical treatment significantly improved the formation of nanorods/nanotubes which eventually increase the electrical conductivity (5.433 × 10-2 – 1.708 × 10-1 S/cm) as compared to those without chemical treatment (3.655 × 10-2 S/cm). Among all the PAni with chemical treatment, fullerene doped PAni that treated with CSA shows the highest amount of nanorods/nanotubes and electrical conductivity of 1.708 × 10-1 S/cm. Beside, PAni with addition of C60 plays a good synergy effect which significantly enhance the electrical conductivity of PAni nanocomposites as iv compared to PAni with addition of S.G.F. The electromagnetic interference (EMI) shielding properties of fullerene doped PAni nanocomposites were carried out by Microwave Vector Network Analyzer (MVNA) from frequency range of 0.5 GHz to 18.0 GHz. Based on the result, PAni nanocomposites with 40 % of C60 that was treated with CSA possesses the poorest EMI shielding properties with a broad and weak reflection loss (RL) peak of -6.3 dB. This is because the lowest electrical conductivity, dielectric permittivity and heterogeneity of PAni nanocomposites will possess the weakest molecular polarization that leads to the poorest EMI shielding. However, PAni formulated with 10 % of C60 that was treated with CSA revealed a narrow and sharp RL peak with the highest absorption (-61.3 dB) at 9 GHz. It is because the highest electrical conductivity (1.708 × 10-1 S/cm), dielectric permittivity and heterogeneity (larger amount of nanorods/nanotubes) of PAni will induce more disordered motion of charge carrier along the PAni backbone, thus enhanced EMI shielding properties.